Progress against nutrition for growth commitments - Fanzo, Jessica; Arakelian, Meghan (International Food Policy Research Institute, 2015)
The issue of nutrition had an important moment in the spotlight in 2013. At the nutrition for growth (N4G) summit in London that year, governments, UN agencies, civil society organizations, businesses, donors, and other organizations gathered to consider how to improve nutrition worldwide. Ninety of these stakeholders signed the Global Nutrition for Growth Compact, in which they publicly committed to take concrete action against malnutrition. And the momentum spread further: an additional 20 stakeholders made commitments after the compact was formulated and published.